2018
DOI: 10.1371/journal.pone.0198819
|View full text |Cite
|
Sign up to set email alerts
|

Genetic profile of scrapie codons 146, 211 and 222 in the PRNP gene locus in three breeds of dairy goats

Abstract: Polymorphisms at PRNP gene locus have been associated with resistance against classical scrapie in goats. Genetic selection on this gene within appropriate breeding programs may contribute to the control of the disease. The present study characterized the genetic profile of codons 146, 211 and 222 in three dairy goat breeds in Greece. A total of 766 dairy goats from seven farms were used. Animals belonged to two indigenous Greek, Eghoria (n = 264) and Skopelos (n = 287) and a foreign breed, Damascus (n = 215).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 45 publications
(60 reference statements)
1
14
0
Order By: Relevance
“…Genotypic and allelic frequencies regarding codons 37, 110, 127, 137, 142, 146, 154, 168, 194, 211, 215, 222, and 240 were calculated within and across breed, based on counting the respective genotypes of individual animals. The Hardy–Weinberg equilibrium state was examined at each codon and breed using a chi-square test ( p ≤ 0.05): where O is the observed number of each genotype; E is the expected number of each genotype assuming Hardy–Weinberg equilibrium; and Σ is the summation over all possible genotypes [ 48 , 49 ] (R software v4.0.3). This type of statistical analysis is very important in selection studies in order to evaluate the possible inbreeding, the possible transmission of unfavorable linked traits, and in order to assess the genetic variability conservation.…”
Section: Methodsmentioning
confidence: 99%
“…Genotypic and allelic frequencies regarding codons 37, 110, 127, 137, 142, 146, 154, 168, 194, 211, 215, 222, and 240 were calculated within and across breed, based on counting the respective genotypes of individual animals. The Hardy–Weinberg equilibrium state was examined at each codon and breed using a chi-square test ( p ≤ 0.05): where O is the observed number of each genotype; E is the expected number of each genotype assuming Hardy–Weinberg equilibrium; and Σ is the summation over all possible genotypes [ 48 , 49 ] (R software v4.0.3). This type of statistical analysis is very important in selection studies in order to evaluate the possible inbreeding, the possible transmission of unfavorable linked traits, and in order to assess the genetic variability conservation.…”
Section: Methodsmentioning
confidence: 99%
“…[36] Goats with amino acid variations present at positions 146, 211, and 222, as well as several other sites, show reduced susceptibility to either BSE or sheep scrapie. [24,37,38] Sheep with variations at position 136, 154, and 171, among others, present with a range of susceptibilities to classical scrapie-including, in the case of A 136 R 154 R 171 homozygous sheep, near-complete resistance to infection. [39][40][41] The latter finding has led to a multinational effort to breed sheep towards resistance to classical scrapie infection in areas where the disease is endemic, resulting in a significant decline and near-eradication of the disease in countries employing targeted breeding programs.…”
Section: Introductionmentioning
confidence: 99%
“…However, the latter studies involved mostly small samples (n = 51 -436 goats) of crossbred and undefined goat populations in Greece. Vouraki et al (2018) reported frequencies of approximately 6% for the resistant allele 222K estimated over a larger population sample (n = 551 goats) of two indigenous Greek breeds (Eghoria and Skopelos). A follow-up study on the same dataset found no associations of allele 222K with dairy traits (Vouraki et al, 2019).…”
mentioning
confidence: 93%
“…However, diverse frequencies of these alleles have been observed among and within breeds and countries. Thus, breed-specific studies are necessary for the development of selection schemes in each country (Ricci et al, 2017;Vouraki et al, 2018). Studies of both healthy and affected Greek goats have reported mutations that lead to amino acid substitutions in over 20 codons of the caprine PRNP gene, including the ones that have been associated with scrapie resistance (222K, 146S/D, 211Q) (Billinis et al, 2002;Bouzalas et al, 2010;Fragkiadaki et al, 2011;Kanata et al, 2014).…”
mentioning
confidence: 99%